The phenomenon of childhood and adolescence as presented in Belarusian narratives about the Great Patriotic War - Baharadava, Tatsiana Robertovna (Journal of the Belarusian State University. Philology, 2019)
The article dwells on the problem of childhood and adolescence as presented in Belarusian war narratives. The author of the article does the literary research of the topic of childhood and adolescence in the context of war and post-war time. This topic in the texts is revealed via the perception of writers who faced war in either their childhood or in their youth and via children’s understanding of war. The author analyses the methods of war reality depiction given from the retrospective viewpoint in the works of Belarusian writers. The research novelty lies in the fact of stating the literary devices used by Belarusian authors in creating war context through the comparative historical aspect. The author finds out the tendencies of artistic understanding and depicting reality in diverse works about war.
Keywords: double vision; eidetic image; shift of consciousness; stream of consciousness; syncretism; retransmission; lyrical principle of typification